2018
DOI: 10.1007/s11060-018-2879-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the Glasgow Prognostic Score for glioblastoma multiforme patients treated with radiotherapy and temozolomide

Abstract: The GPS appeared to be useful in prognostic stratification of GBM patients into three groups with significantly different survival durations resembling the RTOG RPA classification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…GB is the deadliest of all brain tumors, with a median patient survival up to 16 months, even with treatment (Topkan et al, 2018). Here, we demonstrated multiple pathways of host and GB-CD73 contribution to GB pathogenesis, such as GB angiogenesis, invasion, and its chemoresistance.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…GB is the deadliest of all brain tumors, with a median patient survival up to 16 months, even with treatment (Topkan et al, 2018). Here, we demonstrated multiple pathways of host and GB-CD73 contribution to GB pathogenesis, such as GB angiogenesis, invasion, and its chemoresistance.…”
Section: Discussionmentioning
confidence: 71%
“…Further, the impermeability of the blood-brain barrier (BBB) makes chemotherapeutic drug delivery challenging for GB treatment (Neuwelt et al, 1982). Currently, the median survival for GB patients is 16 months even with treatment (Topkan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have also found similar results for the prognostic role CAR or GPS in various types of cancers. [7][8][9][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] This highlighted the general prognostic role of these two inflammation-based scores in malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Even though preceding research confirmed the individual poor prognostic worth of both elevated CRP and reduced Alb levels [24][25][26][27][28][29], to our best information, the present study represents the first attempt to assess the prognostic value of CRP/Alb in newly diagnosed GBM patients intended to undergo RT and TMZ. Only recently, Xu et al [33] and Topkan et al [34] examined the prognostic essentialness of Alb as a component of prognostic indices. In Xu's study, two combined prognostic indices, namely, the albumin-to-globulin ratio (AGR) and Onodera's prognostic nutritional index (PNI), were examined, and both the low AGR (<0.75) and PNI (<48) were reported to be associated with inferior OS durations in GBM [33].…”
Section: Discussionmentioning
confidence: 99%
“…In Xu's study, two combined prognostic indices, namely, the albumin-to-globulin ratio (AGR) and Onodera's prognostic nutritional index (PNI), were examined, and both the low AGR (<0.75) and PNI (<48) were reported to be associated with inferior OS durations in GBM [33]. In the more recent study, Topkan et al [34] tested the prognostic value of the Glasgow Prognostic Score (GPS), a combination of CRP and Alb, in 142 newly diagnosed GBM patients treated with RT and concurrent plus adjuvant TMZ. In this study, the GPS was found to be useful in prognostic stratification of GBM patients into three distinctive survival groups (P < 0.001), which resembled the RTOG RPA classification.…”
Section: Discussionmentioning
confidence: 99%